PENGARUH LEVERAGE, GOOD CORPORATE GOVERNANCE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Zulfikri Roskha; Zulbahridar '; Hariadi Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study is to investigate the influence of leverage, good corporate governance, and firm size on earnings management. In the good corporate governace is proxied into institutional ownership, manegerial ownership, independent directors, audit quality, and commisioners. The population of this study is the manufacturing comapanies which are listed in Indonesia Stock Exchange in 2012 to 2014. The samples selection of this study is performed by using purpose sampling methode, consisted of 21 companies have been chosen based on selected according to the criteria of the sample from 141 populations. The methode analysis used in this study is multiple regression analysis. The coefficient of determination is 30%, in term of adjuted R square. This showed that dependent variable has low ability in explaining the variation of variables. Partially, the result of the study reveal that leverage, institutional ownership, manegerial ownership, audit quality, and firm size influence to the earnings management. And the other side, independent commisioners and board of commissioners aren’t influence to the earnings management. Simultaneously, the result of the study reveal that leverage, institutional manegerial ownership, independent commissioners, audit quality, board of commissioner, and firm size influence to the earnings management.Keyword : leverage, governance, size, and earning management